The most metal-poor Galactic globular cluster: the first spectroscopic observations of ESO280-SC06. Issue 4 (3rd April 2018) - Simpson, Jeffrey D
Abstract: We present the first spectroscopic observations of the very metal-poor Milky Way globular cluster ESO280-SC06. Using spectra acquired with the 2dF/AAOmega spectrograph on the Anglo-Australian Telescope, we have identified 13 members of the cluster, and estimate from their infrared calcium triplet lines that the cluster has a metallicity of $[\textrm{Fe}/\textrm{H}]=-2.48^{+0.06 }_{ -0.11}$ . This would make it the most metal-poor globular cluster known in the Milky Way. This result was verified with comparisons to three other metal-poor globular clusters that had been observed and analysed in the same manner. We also present new photometry of the cluster from EFOSC2 and SkyMapper and confirm that the cluster is located 22.9 ± 2.1 kpc from the Sun and 15.2 ± 2.1 kpc from the Galactic Centre, and has a radial velocity of $92.5^{+2.4 }_{ -1.6}$ km s −1 . These new data finds the cluster to have a radius about half that previously estimated, and we find that the cluster has a dynamical mass of the cluster of (12 ± 2) × 10 3  M⊙ . Unfortunately, we lack reliable proper motions to fully characterize its orbit about the Galaxy. Intriguingly, the photometry suggests that the cluster lacks a well-populated horizontal branch, something that has not been observed in a cluster so ancient or metal poor.